Automátic generatión of two-dimensional enclosures between bodies in contact . Application to heat radiation Computer program "SPADE" - Callwood, N. H.; Pissanetzky, Sergio (Comisión Nacional de Energía Atómica (Argentina), 1981)
Fil: Callwood, N. H. Comisión Nacional de Energía Atómica; Argentina